Paleobotanical fossils in the municipality of Duque Bacelar/MA: survey, importance and awareness of the academic community regarding their preservation (Research, Society and Development, 2022)
The APA dos Morros Garapenses has fossils of pteridophytes and gymnosperms of Permian age, but which has little recognition even by the local community and lacks further studies in the area. In this sense, the focus of this research is to carry out a survey of plant fossils present in the aforementioned area and present them to the academic community, with the objective of transmitting knowledge and raising awareness of the importance of preservation. The quali-quantitative study was developed in the municipality of Duque Bacelar - MA, where the occurrence of fossils was verified and its target audience was academics with a degree in Biological Sciences from the State University of Maranhão - UEMA, Coelho Neto campus. Electronic questionnaires via google forms and a field visit to the MUHNAP/Museum of Natural and Environmental History of Vale do Parnaíba were used as data collection instruments, where some specimens collected are cataloged. Analyzing the students' initial perception of the plant fossils present in the APA, through the application of a questionnaire, it was observed that most of them had no knowledge of them, despite being part of their city and region. In this regard, educational materials were prepared (video and booklet), with relevant information about the heritage present in the region and made available to students. The materials were disseminated online, via social networks, WhatsApp and Instagram. The results were satisfactory, the students showed interest in the material and left a positive opinion about it, in a second questionnaire made available to them, also online.